Designing Liquid‐Infused Surfaces for Medical Applications: A Review. Issue 50 (27th August 2018) - Howell, Caitlin; Grinthal, Alison; Sunny, Steffi; Aizenberg, Michael; Aizenberg, Joanna
Abstract: The development of new technologies is key to the continued improvement of medicine, relying on comprehensive materials design strategies that can integrate advanced therapeutic and diagnostic functions with a variety of surface properties such as selective adhesion, dynamic responsiveness, and optical/mechanical tunability. Liquid‐infused surfaces have recently come to the forefront as a unique approach to surface coatings that can resist adhesion of a wide range of contaminants on medical devices. Furthermore, these surfaces are proving highly versatile in enabling the integration of established medical surface treatments alongside the antifouling capabilities, such as drug release or biomolecule organization. Here, the range of research being conducted on liquid‐infused surfaces for medical applications is presented, from an understanding of the basics behind the interactions of physiological fluids, microbes, and mammalian cells with liquid layers to current applications of these materials in point‐of‐care diagnostics, medical tubing, instruments, implants, and tissue engineering. Throughout this exploration, the design parameters of liquid‐infused surfaces and how they can be adapted and tuned to particular applications are discussed, while identifying how the range of controllable factors offered by liquid‐infused surfaces can be used to enable completely new and dynamic approaches to materials and devices for human health. Abstract : Liquid‐infused surfaces provide a new platform for designing biomedical materials that not only prevent fouling by physiological fluids, microorganisms, and cells, but also permit the integration of antifouling capabilities with surface functionalities such as dynamic adaptability, drug release, improved optical and mechanical properties, and immune response modulation. These materials can enable new approaches to medical devices with applications from diagnostics to surgical equipment and implants.